Street Vendor Control Procedures in Sidoarjo Regency: Prosedur Pengendalian Pedagang Kaki Lima di Kabupaten Sidoarjo - M. Adi Santoso; Emy Rosnawati (Academia Open, 2025)
General Background: Street vendor governance constitutes a central issue in urban public order management and local regulatory enforcement in developing regions. Specific Background: In Sidoarjo Regency, the Municipal Police Unit (Satpol PP) is mandated to maintain public order while addressing the presence of vendors operating in restricted public spaces under regional regulations. Knowledge Gap: Despite frequent regulatory actions, limited empirical descriptions exist regarding the procedural stages, operational strategies, and ethical considerations applied during enforcement at the local level. Aims: This study seeks to examine the strategies, procedures, and approaches implemented by Satpol PP in controlling street vendors in prohibited areas. Results: Findings reveal that enforcement is conducted progressively through socialization, warnings, routine patrols, public reporting mechanisms, confiscation procedures, and inter-agency coordination, accompanied by preventive education and relocation efforts to designated zones. A persuasive and humanistic approach is consistently prioritized to balance regulatory compliance with vendor rights and to minimize social conflict. Novelty: The study provides a detailed qualitative account of staged enforcement practices that integrate legal authority, administrative procedures, and social considerations within a single local governance framework. Implications: These insights offer practical guidance for policymakers seeking to manage informal economic activities while preserving public order, social stability, and equitable treatment of vulnerable urban workers. Highlights: Regulatory actions follow sequential stages from outreach to confiscation when violations persist. Continuous monitoring relies on patrol activities, community reports, and surveillance systems. Preventive measures include education programs and allocation of designated trading locations. Keywords: Street Vendors; Municipal Police; Public Order; Local Regulation Enforcement; Informal Economy